Thermal analysis of li-ion battery pack using phase change materials based on climate conditions - Mohammed Mokhtar Benounnane, Ishak; Wahid Belarbi, Ahmed; El Bachir Ghribi, Mohammed (Bulletin of Electrical Engineering and Informatics, 2025)
The development of lithium-ion batteries necessitates improved management of these systems, particularly with regard to thermal aspects. They operate optimally between 35 °C and 45 °C. Temperatures exceeding 50 °C accelerate cell aging, while those surpassing 60 °C can trigger thermal runaway, potentially leading to catastrophic failure. To mitigate these risks, phase change materials (PCMs) are employed in battery thermal management systems (BTMS). They absorb heat during charging or discharging, transitioning from solid to liquid, then release the stored energy during periods of low demand, solidifying to help regulate battery temperature. This study conducts a thermal analysis of a lithium-ion (LiFePO4) battery pack delivering a 24 V load, using COMSOL MULTIPHYSICS software. The objective is to evaluate and compare the thermal behavior of different PCMs, RT27, Paraffin Wax 58-60, and HM030, against air as a baseline reference. Simulations are performed using the integrated finite element method (FEM), with a discharge rate of 4 C. A correlation is proposed between the choice of PCM and the climate in specific locations, with the choice being made based on the disparities in the results obtained.